Friends during Early Adolescence - Suzanna Smith (EDIS)
“If you have a son or daughter between the ages of 10 and 14, you probably have heard, “But Mom, Dad, all my friends do, have, or wear…” something you don’t want them to do, have, or wear.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, March 2012.